Governance in educational institutions in Portugal - Eva García Redondo (Springer, 2016)
The present study addresses the governance processes governing the organization and management of educational institutions in Portugal, in a context of analysis in which the educational reforms carried out in this country, from the early nineteenth century (when school responsibility is assumed exclusively by the State) to the present, play what we estimate a central role. It is in response to this reality, on the basis of which we study their meaning and state. Evaluation, privatization and autonomy are the vectors which, we believe, provide the frame for a market speech in which we intend to emphasize, considering, on the one hand, that the management of education is conditioned by political developments and interests, of one kind or another, and, on the other hand, that the evolution of governance in its various institutions, although in progress, is gradually adapting to the standards set down at European level in varying degrees of intensity.